Too bold for the box office : the mockumentary from big screen to small - Miller, Cynthia J., 1958- (Scarecrow Press, Inc., 2012)
In Too Bold for the Box Office, Cynthia J. Miller has assembled essays by scholars and filmmakers who examine the unique cinematic form of mockumentary. Individually, each of these essays looks at a given instance of mockumentary parody and subversion, examining the ways in which each calls into question our assumptions, pleasures, beliefs, and even our senses. Writing about national film, television, and new media traditions as diverse as their backgrounds, this volume's contributors explore and theorize the workings of.